2021
DOI: 10.21831/jrpm.v8i1.14995
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of proportional reasoning ability of junior high school students

Abstract: This study aims to describe proportional reasoning skills and students’ difficul­ties in solving proportional reasoning problems. The population of this research was 3480 seventh-grade students of state junior high schools in the Yogyakarta region. The samples were 158 students chosen using proportionate stratified random sampling that represent four categories of school (very high, high, me­dium, low) based on the average scores of the national examination in mathe­matics in 2016. Data were collected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The two proportions stated in the two figures above are formed from direct proportion relationships, so they are not in accordance with the context of the problem given which should use indirect proportion relationships. The finding of research (Mardika & Mahmudi, 2021) also showed the same thing that students are more proficient in solving direct proportion problems than indirect proportion. The unique in this study is that there are no students who can state the indirect proportion relationship given in the problem.…”
Section: Students' Answers To the Sixth Problemmentioning
confidence: 81%
See 2 more Smart Citations
“…The two proportions stated in the two figures above are formed from direct proportion relationships, so they are not in accordance with the context of the problem given which should use indirect proportion relationships. The finding of research (Mardika & Mahmudi, 2021) also showed the same thing that students are more proficient in solving direct proportion problems than indirect proportion. The unique in this study is that there are no students who can state the indirect proportion relationship given in the problem.…”
Section: Students' Answers To the Sixth Problemmentioning
confidence: 81%
“…In mathematics learning, students often have difficulties in solving proportional reasoning problems. The difficulties faced by students are in finding multiplicative relationships, understanding inverse value comparisons, and explaining the results obtained (Mardika & Mahmudi, 2021), distinguishing proportional from nonproportional situations (Tjoe & Torre, 2014). Frequent errors in solving proportional reasoning problems are caused by confusion in identifying unit values and algorithmbased errors in the computational process (Soyak & Isiksal, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are able to connect problems with their own experience since the problem context is familiar to them. The problem solving strategies chosen by students are always based on the experiences and routine habits of students in solving simple problems rather than solving complex problems (Chai & Kong, 2017;Mardika & Mahmudi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Berapa harga 2 buku Ani?" [15]. Dalam menyelesaikan soal tersebut, siswa hanya menjumlahkan dan mengurangi angka, tanpa menggunakan proporsi.…”
Section: Pendahuluanunclassified